Impact of Polyelectrolytes on the Effectiveness of Treatment of Groundwater with Increased Natural Organic Matter Kontent = Wpływ polielektrolitów na skuteczność oczyszczania wody podziemnej o podwyższonej zawartości naturalnej materii organicznej - Krupińska, Izabela (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The article discusses effectiveness of treatment of groundwater with increased natural organic matter content with the use of organic polyelectrolytes. The effects of water treatments were determined by the ionic character of the polyelectrolyte and its dose. Due to the amount of removed general ferric and coloured matters a greater usefulness of anionic and non-ionic polyelectrolytes was shown, while due to decreased turbidity and TOC, cationic flocculants proved more useful.
Keywords: groundwaters; natural organic matter; polyelectrolytes cationic; anions; nonionics; coagulation; wody podziemne; naturalna materia organiczna; polielektrolity kationowe; aniony; polielektrolity niejonowe; koagulacja